The State and Local Self-Government. Territorial Organization of the State - Kaminski, Radoslaw (Polish political science, 2019)
Local self-government constitutes a part of executive power in the state, with the state’s law underlying its functioning. Local government remains under the state’s supervision, representing a form of the political system within the decentralized public administration. 2018 marks 20 years of the functioning of local self-government based on a three-tier structure. The aim of the paper is an attempt at finding the answer to the question whether or not the organizational solutions adopted by the legislator and established in practice need to undergo reforms and if so, to what extent? The question thus formulated relates directly to the argument that the organization of local government system is not sound while the criteria assumed in the territorial breakdown of the local government organization do not correspond to the conditions in which those units operate, and therefore what appears necessary is for the system to be reorganized and the number of units at individual tiers to be reduced. The paper presents selected problems of the local administration in the context of a systemic organization and suggest possible (or necessary) changes which, in the author’s view, should become a subject of discussion (and in practice are such) between local selfgovernment and government administration.